A presença e a ausência do reconhecimento social : os discursos docentes na coluna “Palavra de professor” (Jornal Extra Classe, SINPRO/RS, 2006 – 2015) - Cuty, Jerusa Alves (2017)
The research had as proposal to investigate the social recognition of the teacher through the teaching discourses in the column "Word of Professor" of the Extra Class Journal, SINPRO / RS. Thus, the total corpus of the research of the dissertation is composed of twenty-three texts, collected in the online version, selected during the production of ten years, from 2006 to 2015, taking into account words that show the term recognition or its derivatives. As a research problem, we questioned: What are the evidences of the implication of the spheres of recognition, in the intersubjective context, through the writings of teachers of private education in the said column? The general objective proposed for this research was to investigate indicators of presence or absence of recognition. The research presents as specific objectives that helped to delimit the theme: a) to know the place of the teacher within the marks indicated in the speeches printed in the column "Word of teacher"; b) analyze how the teacher sees and places himself in the process of social recognition. As a theoretical framework, the German philosopher Axel Honneth was chosen, with his Theory of Recognition, in which the thinker proposes the spheres of recognition that have been focused as a priori categories, which demonstrate an imbrication between the intersubjective context (love, law and esteem social) and the subjective context (self-confidence, self-respect and self-esteem) of a social matrix. With these indicators, we aimed to know the evidences of recognition, in the intersubjective context, that appear in the column and, similarly, it was intended to identify the elements that demonstrate the subjective context of the teacher relationship in any inter-relational context. As a posteriori categories, created from Content Analysis (AC), with Laurence Bardin as the main exponent, the research involved the treatment of the data to focus the effects of sense of recognition, which was put in confluence with the spheres of recognition of Honneth. It was thus deduced that love of the profession, the first sphere of the Theory of Recognition, underlies most teachers, but they wish to have their rights guaranteed and wish to have social esteem present.